Religion, Congestive Heart Failure, and Chronic Pulmonary Disease - Koenig, Harold G. (Journal of religion and health, 2002)
Objective: To examine the prevalence of religious beliefs and practices in hospitalized patients with congestive heart failure (CHF) or chronic pulmonary disease (CPD), and determine relationships with physical and mental health. Methods: Subjects were a consecutive sample of 196 patients age 55 or over admitted to Duke University Medical Center with a diagnosis of CHF or CPD. Patients underwent a 60-90 minute interview and physical exam to assess physical health, social support, mental health, religious activities and attitudes (attendance, prayer and scripture study, intrinsic religiosity). Results: Religious practices were widespread; 98% had a religious affiliation; 48% reported attending religious services weekly or more; 70% reported praying or reading religious scriptures at least daily; and over 85% consistently indicated intrinsic religious beliefs and attitudes. Religious activities and attitudes were inversely related to measures of physical illness severity and functional disability, and were less common among patients with prior psychiatric problems, hospitalizations for depression, drinking problems, and those currently taking psychotropic drugs. Religious activities (especially religious attendance) were associated with greater social support, but were only weakly related to less depression. Conclusions: Religious beliefs and activities are common among patients with CHF and CPD, are associated with less severe illness and functional disability, fewer prior psychiatric problems, and less psychotropic drug use. Treatment implications are discussed.